2014
DOI: 10.1186/1471-2458-14-931
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tobacco smoking among health-care physicians in Bahrain

Abstract: BackgroundThere is a clear shift in smoking habits among the Middle Eastern population with a recent and alarming increase in the prevalence of waterpipe (shisha) smoking. This phenomenon has not yet been studied sufficiently across the physician population. Therefore, we set out to establish the smoking status of primary healthcare physicians in the kingdom of Bahrain.MethodsA self-administered questionnaire was distributed to a random sample of 175 out of the total 320 primary care physicians. Descriptive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
3
37
1
2
Order By: Relevance
“…Evidence suggests that water pipe smoking is gaining popularity among populations that may "resist" cigarette smoking as the former is mistakenly perceived a healthier option for tobacco use. The increased popularity has been reported among physicians, [25] and medical students. [26] The academics in a university in a neighboring country have also been reported to smoke the waterpipe at a prevalence of 13.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that water pipe smoking is gaining popularity among populations that may "resist" cigarette smoking as the former is mistakenly perceived a healthier option for tobacco use. The increased popularity has been reported among physicians, [25] and medical students. [26] The academics in a university in a neighboring country have also been reported to smoke the waterpipe at a prevalence of 13.5%.…”
Section: Discussionmentioning
confidence: 99%
“…9 It further suggested that the exposed rate of smoking is higher among males (33.5%) compared with females (11.9%) age between 13-15 years. 10 Global Youth Tobacco Survey (GYTS), Nepal (2001) had reported 16.3 % prevalence of tobacco use among the high school students 11 and GYTS, Nepal (2011) revealed that 10% of student currently use any form of tobacco, nine percent currently use smoked tobacco product and 16.2% use smokeless tobacco product currently. In Terai region of Nepal, tobaccos are using in various forms of smoked and smokeless tobaccos.…”
Section: Introductionmentioning
confidence: 99%
“…The tobacco used for water‐pipe smoking (WPS) contains 2% to 4% nicotine. WPS is common in many Middle Eastern countries, including Bahrain, Egypt, Israel, Jordan, Kuwait, Lebanon, Qatar, Saudi Arabia, and the United Arab Emirates 1–8 . However, it is pertinent to mention that, because of the increasing popularity of WPS as a behavioral/recreational activity, this form of smoking has made its way into several Western countries, including Australia, Canada, the United Kingdom, and the United States 9–15 .…”
mentioning
confidence: 99%